Satellite multitasking fuzzy system for attitude and sun tracking - Chak, Yew-Chung; Varatharajoo, Renuganth (International Society of Multiphysics, 2024)
Almost all high-precision pointing satellites use reaction wheels to produce the desired commanded control torque to stabilize their pointing direction. The reaction wheels are good actuators; however, one or two wheels may fail sometimes and could jeopardize the space missions. The solar arrays in low Earth orbiting satellites are typically mounted on the pitch-axis and their rotations are driven by the solar array drive assemblies (SADAs). Although the SADAs generate internal torques due to the rotations, they can potentially be manipulated for the disturbance compensation. In this work, three disturbance rejection control schemes are proposed for the low Earth-orbiting satellite using the combined attitude and sun tracking control system (CASTS). These disturbance compensation schemes are active torque control, linear quadratic integral, and disturbance observer-based control. A multitasking fuzzy fusion framework is introduced to address situations with multiple disturbance rejection control schemes. Numerical treatments of the proposed disturbance compensation strategies are presented. The results show that the disturbance compensation schemes are effective in controlling the attitude and tracking the Sun simultaneously.